Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1073/pnas.84.2.570
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to Epstein-Barr virus-determined nuclear antigen (EBNA)-1 and EBNA-2 in acute and chronic Epstein-Barr virus infection.

Abstract: Five distinct Epstein-Barr virus (EBV)-deterinned nuclear antigens (EBNA-1 to were recently identified. Antibody responses to these antigens could conceivably differ, and thus prove of serodiagnostic value, in EBVassociated disease processes. As a rst step, murine or human cell lines transfected with appropriate EBV DNA fragments and stably expressing either EBNA-1 or EBNA-2 were used to determine the frequency and time of emergence of antibodies to these two antigens in the course of acute and chronic infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
1
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(138 citation statements)
references
References 33 publications
6
127
1
3
Order By: Relevance
“…However, we speculated that the induction of the EBNA1 response might be delayed because this requires prior Ag release and, arguably, such release may depend upon an effective CTL response to latently infected cells having already been mounted. This would provide an interesting parallel to the humoral response to primary infection, in which Abs to EBNA1, but not to the other EBNAs, develop unusually late (36,37). In fact, we consistently observed that the primary CTL response to the B*3501-restricted EBNA1/HPV epitope was at least as strong as that seen in the same individuals to the EBNA3A/YPL epitope and comparable to other immundominant latent epitopes.…”
Section: Discussionsupporting
confidence: 52%
“…However, we speculated that the induction of the EBNA1 response might be delayed because this requires prior Ag release and, arguably, such release may depend upon an effective CTL response to latently infected cells having already been mounted. This would provide an interesting parallel to the humoral response to primary infection, in which Abs to EBNA1, but not to the other EBNAs, develop unusually late (36,37). In fact, we consistently observed that the primary CTL response to the B*3501-restricted EBNA1/HPV epitope was at least as strong as that seen in the same individuals to the EBNA3A/YPL epitope and comparable to other immundominant latent epitopes.…”
Section: Discussionsupporting
confidence: 52%
“…Henle et al (1987), using an immunofluorescence test similar to that of Dillner et al (1987) and Seigneurin et al (1987), demonstrated the presence of anti-EBNA 2 antibodies in 71 ~ of healthy EBV-immune controls, but neither NPC nor BL sera were included in their study. The different results obtained with NPC and BL sera with the two types of assay are not due simply to differences in sensitivity, since the immunoblotting assays actually detected a decreased anti-EBNA 2 response in NPC sera, which is in contrast to the increased incidence of antibodies reported using immunofluorescence tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, some immunoblotting studies have found that 2% of subjects who have De Paschale M et al . Epstein-Barr virus serological diagnosis experienced previous infections may be negative for VCA IgG (anti-p23 or anti-p18) [23] and, although rare, this pattern can be found in routine laboratory tests and may represent about 1.7% of all EBNA-1 IgG-positive samples [39] . An isolated EBNA-1 IgG pattern therefore gives rise to some interpretative doubts: it is possible to envisage aspecific EBNA-1 IgG, a lack of VCA IgG production or their loss over time.…”
Section: Isolated Ebna-1 Iggmentioning
confidence: 99%
“…Children and adults with primary infection are not always positive for VCA IgM [32,38] . Anti-EBNA-2 IgG (EBNA-2 IgG) appear early, and may be present in up to 30% of the patients in the course of disease [2,23] , whereas anti-EBNA-1 IgG (EBNA-1 IgG) is usually undetectable during the first 3-4 wk after the onset of clinical symptoms [32,39] and is therefore indicative of past infection. Furthermore, most patients with chronic infection and immunosuppressed patients are negative for EBNA-1 IgG or have only low levels [40] .…”
Section: Introductionmentioning
confidence: 99%